Uji Organoleptik Dodol Jagung - Ayu Citra Ananda; Anni Faridah (Universitas Negeri Padang, 2020)
Corn was an agricultural product whose production continues to increase in indonesia, including in west sumatra. Corn was varied into food products. The corn content was quite high compared to other food ingredients. The used of corn in dodol processing will added to the selling value and nutrition of dodol. This studied discusses analyzing the used of 300 gr, 350 gr, and 400 gr corn on the quality of shape, color, aroma, texture and taste of dodol. This typed of researched was pure researched using a one-factor complete researched method. The typed of data used was primary data obtained directly from 6 panelists obtained with the organoleptic test format. The results showed that nothing affected the quality, color, aroma, texture, and taste. The best researched results on training the used of corn as much as 400 gr.